QOLP-14. FROM SYMPTOMS TO RADIOTHERAPY: A QUALITATIVE ASSESSMENT OF PATIENT EXPERIENCE IN NEWLY DIAGNOSED HIGH-GRADE GLIOMA. (9th November 2020) - Chainey, Jonathan; Kim, Michael; Chan, Vivien Ka-Ying; Au, Karolyn
Abstract: INTRODUCTION: Considering the poor prognosis of high-grade gliomas, past studies focusing on the felt experience and supportive care needs of patients concentrated on the end-of-life period. Little is known on these subjects during the initial acute portion of the patient's journey, from symptom onset, through surgery, to chemoradiation. This period is one of substantial anxiety for patients and their caregivers, and one during which they struggle to comprehend a large amount of information and navigate a complex situation. METHODS: Adult patients with a new histopathological diagnosis of high-grade glioma who underwent radiotherapy participated in a semi-structured, face-to-face interview. Different segments of the patient's journey were explored, with a focus on patient's emotions, interactions with healthcare providers, satisfaction during the process and access to supports. Descriptive thematic analysis in the tradition of grounded theory was performed. RESULTS: Fifteen patients (7 males, age 34-71 years) were interviewed, and four themes emerged from the analysis. First, information conveyed by the medical team was frequently disconnected from patients' understanding regarding diagnosis and treatment. Second, specific events created a lasting impression that the medical system, and at times medical care providers, lacked empathy. Third, patients' perceptions of shortcomings within the medical system led to decreased trust, particularly regarding the follow-up process. Finally, although respondents identified multiple inadequacies during their journey, they nonetheless acknowledged the great support and quality of services they received. CONCLUSION: This study provides insight into patients' experiences and perceived shortcomings of the medical system, from the time of presentation until the end of radiotherapy treatment in patients with new diagnosis of high-grade glioma. These findings should influence clinicians' attitudes and guide systematic changes including delivery of information and the referral process.